Keefektifan Model Pembelajaran Berbasis Masalah Berbantuan LKS untuk Meningkatkan Kemampuan Koneksi Matematis Siswa - Destia Dwi Rahayu; Yesi Franita; Megita Dwi Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the effectiveness of the problem-based learning model assisted by Student Worksheets (LKS) to improve students' mathematical connection skills on the flat side of cubes and block material. The research design of this present study is a quasi-experimental design with the research population from class VIII students of SMP Negeri 1 Bandongan. The samples in this study were students of class VIII B as the experimental class and VIII C as the control class. The tests used in this study were the One sample t-test and the N-Gain test to see the extent of the increase in the pre-test and post-test scores. The results of the One sample t-test showed that the average of the experimental class > minimum completeness criteria, while in the control class < minimum completeness criteria. The N-Gain test revealed that the average N-Gain value of the experimental class was higher than that of the control class. The results showed that the problem-based learning model assisted by Student Worksheets (LKS) was effective in improving students' mathematical connection skills in the material for building flat sides of cubes and blocks at SMP Negeri 1 Bandongan.